(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This study, entitled “Cooperative Learning: Its Concept, Historical and Philosophical Roots, Implementation Steps, and Tools,” employs a descriptive-analytical approach to examine cooperative learning as a pedagogical strategy. The paper first clarifies the concept of cooperative learning and traces its historical and philosophical foundations through key educational and learning theories. It then highlights the main justifications for its emergence, followed by a discussion of its principles and essential elements. Particular attention is given to the steps, stages, and objectives of implementing cooperative learning, as well as the complementary roles of teachers and students in enriching the educational experience. The study further analyzes the strengths and limitations of this approach, providing a balanced perspective on its applicability in classroom settings. Finally, the paper reviews prominent cooperative learning tools—including cooperative game teams, Jigsaw, Think-Pair-Share, round table, and cooperative integration—which contribute to creating a more interactive, engaging, and effective learning environment.